ROCCIPI Analysis of Surabaya City's Regional Policy on The Implementation of Child Protection - Nastain, Muh; Aini, Haniyah S (University of Merdeka Malang, 2024)
This research was conducted to analyze Surabaya City Regional Regulation Number 3 of 2023 concerning the implementation of child protection using the Rule, Opportunity, Capacity, Communication, Interest, Process, Ideology (ROCCIPI) approach. The research uses qualitative methods with government data sources and participation from the people of Surabaya City. The results of this research are that through the Rule category, the Surabaya City child protection policy has been in existence since 2011 and has been a guideline since then in developing child protection programs, however, detailed evaluation and development of the scope of the regulation is needed. In the Opportunity factor, creating environmental conditions that support regulations and prevent inappropriate behavior needs to be the focus of implementation efforts. In the Capacity or ability factor, it should be noted that involving parties involved with adequate capacity can increase compliance. Then the communication factor or effective communication needs to be improved to ensure that regulations and information related to child protection are conveyed clearly to all parties. Interest factors and processes, the decision-making process also have a big impact. Understanding and managing interests and understanding the decision-making process will help design more effective implementation strategies. Finally, the ideological aspect shows that local values, habits and customs need to be considered in designing an approach that is appropriate to the cultural context of Surabaya society. Therefore, the implementation of Surabaya City's child protection policy still requires evaluation and through the ROCCIPI method, the government can open dialogue and opportunities for partnerships and increase community participation in developing children's policies.